Fatigue is specific to working muscles: no cross-over with single-leg cycling in trained cyclists - Elmer, S. J.; Amann, M.; McDaniel, J.; Martin, D. T.; Martin, J. C. (European Journal of Applied Physiology, 2013)
Fatigue induced via a maximal isometric contraction of a single limb muscle group can evoke a "cross-over" of fatigue that reduces voluntary muscle activation and maximum isometric force in the rested contralateral homologous muscle group. We asked whether a cross-over of fatigue also occurs when fatigue is induced via high-intensity endurance exercise involving a substantial muscle mass. Specifically, we used high-intensity single-leg cycling to induce fatigue and evaluated associated effects on maximum cycling power (P max) in the fatigued ipsilateral leg (FATleg) as well as the rested contralateral leg (RESTleg). On separate days, 12 trained cyclists performed right leg P max trials before and again 30 s, 3, 5, and 10 min after a cycling time trial (TT, 10 min) performed either with their right or left leg. Fatigue was estimated by comparing exercise-induced changes in P max and maximum handgrip isometric force (F max). Mean power produced during the right and left leg TTs did not differ (203 ± 8 vs. 199 ± 8 W). Compared to pre-TT, FATleg P max was reduced by 22 ± 3 % at 30 s post-TT and remained reduced by 9 ± 2 % at 5 min post-TT (both P < 0.05). Despite considerable power loss in the FATleg, post-TT RESTleg P max (596-603 W) did not differ from pre-TT values (596 ± 35 W). There were no alterations in handgrip F max (529-547 N). Our data suggest that any potential cross-over of fatigue, if present at all, was not sufficient to measurably compromise RESTleg P max in trained cyclists. These results along with the lack of changes in handgrip F max indicate that impairments in maximal voluntary neuromuscular function were specific to working muscles.